'By the work, one knows the workman': the practice and profession of the embryologist and its translation to quality in the embryology laboratory. Issue 4 (October 2015) - Go, Kathryn J.
Abstract The embryologist presides over the fulfillment of a patient's treatment in the laboratory for IVF through use of assisted reproduction techniques, and is in a unique position to impart quality to the process. Although the technical skill of the embryologist is critical, the embryologist's contribution to quality is equally conveyed through a knowledge of reproductive biology, keen observation and judgment, astute decision-making, the 'grit' to work under pressure and time constraints, and a sense of mission in the provision and continual development of a safe and effective laboratory. The embryologist also ensures that the laboratory complies with the regulations of federal, state, local and institutional authorities and the recommendations and guidelines of professional associations. In these roles, the embryologist assumes unique responsibilities counterbalanced by the unique rewards of assisting patients in having a family. This article aspires to illuminate this singular profession for those who may be contemplating a career in embryology and act as a resource for those who seek insight into this amalgam of basic science, technical proficiency, and managerial skill and acumen that characterize the practice of clinical embryology and the myriad of ways that practitioners contribute to the quality of assisted reproduction techniques and patient care.